GEGURITAN DUKUH SILADRI KAJIAN NILAI PENDIDIKAN KARAKTER - Ni Wayan Arini (Guna Widya: Jurnal Pendidikan Hindu, 2018)
Traditional Balinese literature is part of Balinese culture which is also a price- less ancestral heritage. In addition, traditional Balinese literature is one form that can be used as a medium in pouring ideas to convey the teachings or norms in the life of society. Literary work is one of the ancestral heritages of a society which is rich in educational values, ingenuity, and social criticism and contains noble virtues that deserve attention in an attempt to preserve and develop the cultural values of the nation, especially the language culture of Bali. A literary work must contain the values of life that apply to the society in which the literary work was created. Such values, for example, represent norms, traditions, rules and beliefs held in a society. These values are, among others, moral values, so- cial values; cultural values / traditions: religious values / religious, and so forth. Similarly, geguritan Dukuh Siladri contains a lot of character education values that can be taught to children, adolescents and adults to be a guide to behave in everyday life. The values of character education contained in Geguritan Dukuh